Differentiated Products and Evasion of Import Tariffs - Javorcik, Beata S.; Narciso, Gaia (World Bank, Washington, DC, 2012)
Emerging literature has demonstrated some unique characteristics of trade in differentiated products. This paper contributes to the literature by postulating that differentiated products may be subject to greater tariff evasion due to the difficulties associated with assessing their quality and price. Using product-level data on trade between Germany and 10 Eastern European countries during 1992-2003, the authors find empirical support for this hypothesis. They show that the trade gap, defined as the discrepancy between the value of exports reported by Germany and the value of imports from Germany reported by the importing country, is positively related to the level of tariff in 8 out of 10 countries. Further, the authors show that the responsiveness of the trade gap to the tariff level is greater for differentiated products than for homogeneous goods. A one-percentage-point increase in the tariff rate is associated with a 0.6 percent increase in the trade gap in the case of homogeneous products and a 2.1 percent increase in the case of differentiated products. Finally, the data indicate that greater tariff evasion observed for differentiated products tends to take place through misrepresentation of the import prices.